Students’ Metalinguistic Awareness in L2 Writing: The Case of Grammarly-Mediated Feedback - Muthiah Hidayatun; Sitti Nurfaidah; Isna Humaera; Muragmi Gazaly (Institut Agama Islam Negeri Kendari, 2021)
This case study aims to explore students’ perceptions of their metalinguistic awareness in L2 writing mediated by Grammarly as online feedback tool. Data garnered from twenty participants’ questionnaire and reflection were analyzed. The findings reveal that the participants perceive the online feedback tool facilitates their drafting process in terms of grammatical awareness. In other words, the online grammar checker could be help to raise their metalinguistic awareness in L2 writing. This study implies that language teacher and teacher educator could utilize this online tool in learning and teaching process in order to raise learners’ metalinguistic awareness as well as learner autonomy.Keywords:Grammarly; L2 writing; metalinguistic awareness; online feedback tool